2017
DOI: 10.1016/j.celrep.2017.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent Basal Stem Cells, Maintained in Localized Proximal Niches, Support Directed Long-Ranging Epithelial Flows in Human Prostates

Abstract: SummarySporadic mitochondrial DNA mutations serve as clonal marks providing access to the identity and lineage potential of stem cells within human tissues. By combining quantitative clonal mapping with 3D reconstruction of adult human prostates, we show that multipotent basal stem cells, confined to discrete niches in juxta-urethral ducts, generate bipotent basal progenitors in directed epithelial migration streams. Basal progenitors are then dispersed throughout the entire glandular network, dividing and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 51 publications
(76 reference statements)
6
72
0
Order By: Relevance
“…As possible evidence that BPH is a reawakening of urethral budding and branching, we demonstrate that the identity of urethral luminal epithelia is established prior to prostate budding in the developing mouse and human ( Figure 4). Evidence from lineage tracing studies of mitochondrial mutations in humans demonstrates a clonal expansion of cells in the proximal urethra to the distal prostate in healthy adults (27,28), but needs confirmation in BPH specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As possible evidence that BPH is a reawakening of urethral budding and branching, we demonstrate that the identity of urethral luminal epithelia is established prior to prostate budding in the developing mouse and human ( Figure 4). Evidence from lineage tracing studies of mitochondrial mutations in humans demonstrates a clonal expansion of cells in the proximal urethra to the distal prostate in healthy adults (27,28), but needs confirmation in BPH specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified cell populations characterized by expression of BMI1 (21), Sca-1 (22,23), TROP2 (24), LY6D (25), and KRT4 (26) that are enriched in the proximal region of the mouse prostate after castration, form spheroids at high frequency, and can act as facultative progenitors in prostate regeneration assays. A proximal to distal expansion of progenitors in human lineage tracing studies has also been demonstrated (27,28).…”
Section: Introductionmentioning
confidence: 88%
“…The resulting mesenchyme cell population will include multiple mesenchymal cell types, i.e., mesenchymal stem cell-like cells, fibroblasts, endothelial cells, nerve cells, and immune cells. Isolation of mesenchymal cell subsets with fluorescence-activated cell sorting (FACS) or magnetic activated cell sorting (MACS), can be performed on the cells as described elsewhere (Kwon, Nelson, DeSantis, Morrissey, & Larsen, 2017;Lee et al, 2017;Moad et al, 2017;Yang, Adam, Ge, Hua, & Fuchs, 2017;Zepp et al, 2017;Zhao et al, 2017).…”
Section: Further Enrichment Of Mesenchymal Cellsmentioning
confidence: 99%
“…Using one-dimensional mathematical models to infer stem cells and progenitor cells dynamics from lineage tracing experiments have been useful in modeling different tissues such as murine epithelial homeostasis of the skin (33), gut (34), human epithelial homeostasis of the epidermis (35) lung (36) prostate (37) and the cornea (38,39). Yet, while these models are insightful, the unique spatial organization in the cornea requires twodimensional models to encompass overall pattern changes.…”
Section: Introductionmentioning
confidence: 99%